Mapping of the occupational risks at clinical and surgical nursing units - a preview note - Zenith Rosa Silvino; Bárbara Pompeu Christovam; Vânia Martins Ferreira (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2005)
Qualitative research that has as study object the occupational risk the one that the professionals of nursing are submitted in the exercise of its activities in the clinic infirmaries and surgery of the University Hospital Antonio Pedro. Objectives: To identify the group and the existing factors of risk in the clinic infirmaries and surgery of the HUAP, To correlate the risks and the damages already occurred in the health of the nursing worker and To argue measured, for priorities, of the risks to be eliminated and/or attenuated. It will be used research-action as method, therefore if it intends through the quarrel of the workers on the proper conditions of work and with the socialization of the experiences, that each one, in particular, discover the social dimension of the proper problems. For this process - quarrel and socialization - it is that the purely individual dimension of the work condition is change into a collective question, that all compromises the group in the brainstorming. One expects with the mapping of the existing risks in the units to have conditions to adjust the limitations of the workers to the exercise of its activities in the hospital, to become the hospital an area more insurance for the health of the worker and to offer subsidies to the institution for one politics of human resources more come back to the occupational health.